1994
DOI: 10.1002/edp.2430030204
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of 4‐month‐old infant responses to hidden silent and sounding people and objects

Abstract: Responses of 4month-old infants to hidden people and objects were investigated with equated task demands. Twenty-one Cmonth~dd infants were administered a combined task, in which they were shown a sounding stimulus that continued to sound after hiding, an auditory task, in which sound was the only m e of information about the position of the object in space, and a vision task, in which a silent stimulus was shown to the infants prior to hiding. Five infant behaviours were coded: reaching, gazing, body movement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 23 publications
1
20
0
1
Order By: Relevance
“…Here, we presented continua that were comprised of creature-like stimuli. There are reasons to suspect that naming effects might be strongest with animate kinds: At 9 months, infants show greater interest for animate over inanimate entities (Ferguson, Graf, & Waxman, 2014; Legerstee, 1994; Sanefuji et al, 2011). Infants are especially attentive to animate-like features (Farroni et al, 2005; Gelman & Opfer, 2002; Molina, Van de Walle, Condry, & Spelke, 2004; Pauen, 2002; Poulin-Dubois, Crivello, & Wright, 2015; Rakison & Poulin-Dubois, 2001; Simion, Macchi Cassia, Turati, & Valenza, 2001; Träuble, Pauen, & Poulin-Dubois, 2014) and already form social categories (Kim, Johnson, & Johnson, 2015; Kinzler, Shutts, & Correll, 2010; Kinzler & Spelke, 2011; Quinn, Yahr, Kuhn, Slater, & Pascalis, 2002; Shutts, Kinzler, McKee, & Spelke, 2009; Waxman, 2013; Waxman & Grace, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we presented continua that were comprised of creature-like stimuli. There are reasons to suspect that naming effects might be strongest with animate kinds: At 9 months, infants show greater interest for animate over inanimate entities (Ferguson, Graf, & Waxman, 2014; Legerstee, 1994; Sanefuji et al, 2011). Infants are especially attentive to animate-like features (Farroni et al, 2005; Gelman & Opfer, 2002; Molina, Van de Walle, Condry, & Spelke, 2004; Pauen, 2002; Poulin-Dubois, Crivello, & Wright, 2015; Rakison & Poulin-Dubois, 2001; Simion, Macchi Cassia, Turati, & Valenza, 2001; Träuble, Pauen, & Poulin-Dubois, 2014) and already form social categories (Kim, Johnson, & Johnson, 2015; Kinzler, Shutts, & Correll, 2010; Kinzler & Spelke, 2011; Quinn, Yahr, Kuhn, Slater, & Pascalis, 2002; Shutts, Kinzler, McKee, & Spelke, 2009; Waxman, 2013; Waxman & Grace, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…From an early age, responses are differentiated in the way that infants communicate with people and act on objects (Legerstee, 1994). That people are treated in a more communicative fashion by infants than objects corresponds to findings of Spelke and her colloborators that infants can distinguish animate from inanimate objects on the basis of their contact, i.e.…”
mentioning
confidence: 84%
“…Research suggests that children distinguish between animate and inanimate causal agents from a very young age. Legerstee (1994) found that 4-month-olds reacted differently when a person or an inanimate object disappeared behind a door, touching the door in response to the object and vocalizing to the person without touching the door. Sixmonth-olds reveal surprise when an inanimate object such as a chair moves spontaneously and 10-month-olds pull or push on knobs trying to activate an inanimate object more than an animate one (Golinkoff, Harding, Carlson & Sexton, 1984).…”
Section: What Does Research Tell Us About Children's Ability To Separmentioning
confidence: 97%